Knowledge, attitude and practice of basic life support among nursing staffs at a tertiary care hospital - Gyawali, Sangya; Shah, Rajat; Shah, Sanjay (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Basic life support is medical care that is provided for life-threatening illnesses or injuries until a medical team arrives. The conditions can be cardiac arrest, respiratory distress or airway obstruction. This care can be provided by trained medical personnel or qualified bystanders. If basic life support is provided on time after prompt recognition of the situation, this helps to increase the chance of survival of the patient.Method: This is a hospital based cross-sectional study done for the duration of three months (June 15, 2023-September 15, 2023). Questionnaire sets were distributed to all the participants after taking ethical clearance and their response was evaluated. The data were analyzed using Statistical Package for the Social Sciences (SPSS version 23). Descriptive statistics were used for demographic variables. Categorical data were presented as number (n) or a percentage (%). Chi-square test was applied between two categorical variables. Pearson’s correlation analysis was used to investigate the relationship between knowledge, attitude and practice.Result: The total number of participants were 145. Our study showed good knowledge 126 (86.9%), good practice 120(82.81%) and poor attitude 90 (62.1%) among the nurses. Significant correlation was seen between knowledge and practice with p value 0.0.Conclusion: The nursing staff had good knowledge and practice regarding basic life support. They had a poor attitude regarding the same. Majority of them have provided basic life support volunta rily and thought it should be a part of their curriculum. Most of them were interested in undergoing basic life support training in a workshop center with hands-on practice under supervision.